Stand-alone rotational atherectomy versus combination with drug-coated balloon angioplasty for the endovascular treatment of heavily-calcified femoropopliteal and popliteal lesions - Kronlage, Mariya; Bertele, Mario; Linden, Fabian; Frey, Norbert; Erbel, Christian (Journal of endovascular therapy, 2023)
Background: Despite major technical advances in the endovascular treatment for peripheral artery disease (PAD), heavy calcification still represents a major obstacle to overcome both due to the high number of periprocedural complications (dissections, embolization, etc) and the limited long-term durability. A promising tool to overcome these obstacles is debulking calcified lesions with atherectomy. Since vessel preparation with atherectomy might even improve the diffusion of antiproliferative substances, we wanted to evaluate the impact of atherectomy±DCB in lower extremity PAD. - Objectives: To explore the safety, efficacy, and long-term durability on treatment of rotational atherectomy in heavily-calcified complex femoropopliteal and isolated popliteal lesions. In addition, we wanted to investigate whether advanced debulking strategies where atherectomy is followed by a drug-coated angioplasty bear an additional advantage over atherectomy and standard percutaneous angioplasty alone in terms of clinical success and freedom from target lesion revascularization. - Results: In total, 218 femoropopliteal and 46 popliteal predominantly heavily-calcified lesions have been investigated. Of 264 cases, in a total of 53 cases, atherectomy treatment was followed by a drug-eluting balloon (DEB) angioplasty (43 in the femoropopliteal and 10 in the popliteal lesions). The lesions were characterized by a significant length (17.3±12.1 cm) and complexity (TASC C in 48.4% and TASC D in 19.7%). During a mean follow-up of 19 (±11) months, a total of 12 patients (4.5%) died. Clinically-driven target lesion revascularization (CD-TLR) was performed in 32 (14.7%) femoropopliteal and 11 isolated popliteal (23.9%) lesions and did not differ significantly between stand-alone atherectomy and atherectomy followed by a DEB. Mean ABI was improved from 0.57±0.22 immediately before intervention to 0.86±0.23 on intervention and remained stable: 0.83±0.16 at follow-up. During follow-up, a mean Rutherford category was reduced from 3.64±1.0 to 2.38±0.98. - Conclusions: Our real-life study provides evidence that atherectomy in combination with DEB is safe and effective but did not have a significant impact on the freedom from target lesion revascularization in our population. Additional large-scale randomized trials are needed to verify these findings. - Clinical Impact - This study investigates the efficacy and safety of combining rotational atherectomy with drug-coated balloon (DCB) angioplasty for treating heavily calcified femoropopliteal and isolated popliteal lesions in peripheral artery disease (PAD). The retrospective analysis of 264 patients highlights the potential of this combination in improving procedural success and reducing periinterventional complications. While demonstrating an excellent procedural and clinical success rate over an average 19-month follow-up, the study finds no significant long-term benefit in freedom from target lesion revascularization (TLR) compared to atherectomy alone. These findings suggest the need for further research to optimize treatment strategies for complex PAD cases, particularly in evaluating the long-term clinical benefits of such combined interventions